Augmented reality in university education - Julio Cabero Almenara; J. Barroso; C. Llorente (Universitat Politècnica de València, 2019)
The increase in use, as well as the possibilities offered by mobile devices, tablets or smartphones in our daily lives, means that these tools can be incorporated, without additional costs, and with great didactic possibilities, in the contexts of university education. This aspect contributes without a doubt, to the proliferation of technologies such as Augmented Reality (AR), which allows, using the aforementioned devices, to facilitate the combination of digital information and physical information in real time. In this article the problem of the conceptualization of the RA wont be presented, but its intended to offer a vision through the analysis of two of the variables that can be considered as limiting in the use of this technology in the university contexts: lack of research, and the few learning objects generated in RA format (all without forgetting the need to have theoretical frameworks to facilitate their educational incorporation). Likewise, its necessary to start from the fact that, if this technology is to be incorporated into university education, its essential that universities create and strengthen production centers that facilitate and/or help the teacher to produce them. And this, not because some objects can not be produced by the teachers themselves, but because complex objects require the management of complex programs, as well as the elaboration of resources of certain, much, difficulty.